Constructal branching design for fluid flow and heat transfer - Antonio F., Miguel (2018)
Our focus is space-filling networks to deliver and distribute flows. Here we report an analytical analysis of optimal branching networks of tubes for both fluid flow and heat transfer. This attempt results in the structural features of these networks, mainly on relationships between the size of the parent and daughter tubes at bifurcations, and the branching angles of the bifurcations. The process of construction of these networks is described for both laminar and turbulent flow, Newtonian and power-law fluids, and constant and pulsatile flows. The extended design rules obtained in this study are compared with the optimal branching rules available in the literature. Structural features of bifurcating tubes under different flow regimes are also analyzed.